A study of a radial clearance leakage of a RV expander - Teo, Olivia Qishan. (2010)
To reduce the detrimental effects that current refrigerants have on the environment, carbon dioxide gas has been proposed as a potential alternative. However, the efficiency of a CO2 refrigeration cycle is relatively low due to the expansion losses. Thus, it is suggested that an expander, particularly a revolving vane expander, can be included in such cycles to replace the expansion valve. In this project, the leakage flow through the radial clearance of a revolving vane expander will be studied. Investigations will be carried out to determine the relationship between the mass flow rate of the leakage flow and the varying parameters, which include varying mesh size, varying angle of radial clearance, varying pressure ratio, varying vertical distance of radial clearance as well as varying velocity of moving boundary. To achieve this, concepts and theories related to the topic will be reviewed. Information learnt from books, journal articles and online articles etc will be presented. Next, a thorough study will be conducted on a paper which detailed the leakage flow through the radial clearance of a rolling piston compressor. This will form the basis of this study and will be a standard to which results are going to be compared against. To determine the mass flow rate of the leakage flow, simulations need to be performed. Gambit and FLUENT are the two software programs that will be used to carry out the simulations before results are collected and compiled. These results will be discussed and conclusions will be drawn.